2022
DOI: 10.3389/fphar.2022.915958
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Colistin Sulfate in Critically Ill Patients: Exposure and Clinical Efficacy

Abstract: Background: Presently, colistin is commercially available in two different forms, namely, colistin sulfate and its sulphomethylated derivative, colistimethate sodium (CMS). However, in the currently reported studies, most of the clinical studies on colistin for parenteral use are referred to as CMS. Data on the pharmacokinetics (PK), clinical efficacy, and side effects of colistin sulfate in clinical use have not been reported.Methods: This retrospective study was performed on carbapenem-resistant organism (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
3
14
1
Order By: Relevance
“…In the present study, the estimated typical value of CL was 1.50 L/h for colistin sulfate, which was lower than the CL of colistin converted from CMS (2.92 L/h) ( Couet et al, 2011 ), and similar to the CL of polymyxin B reported previously (range 1.59–2.86 L/h) ( Wang et al, 2021 ; Chen et al, 2022 ). CrCL was identified to have a significant effect on the CL of colistin sulfate, which was in agreement with a previous study ( Yu et al, 2022 ) and the disposition characteristic of polymyxin B ( Wang et al, 2020 ; Li et al, 2021b ; Yu et al, 2021 ). Monte Carlo simulations demonstrated that the colistin sulfate exposure showed significant negative correlation with renal function.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, the estimated typical value of CL was 1.50 L/h for colistin sulfate, which was lower than the CL of colistin converted from CMS (2.92 L/h) ( Couet et al, 2011 ), and similar to the CL of polymyxin B reported previously (range 1.59–2.86 L/h) ( Wang et al, 2021 ; Chen et al, 2022 ). CrCL was identified to have a significant effect on the CL of colistin sulfate, which was in agreement with a previous study ( Yu et al, 2022 ) and the disposition characteristic of polymyxin B ( Wang et al, 2020 ; Li et al, 2021b ; Yu et al, 2021 ). Monte Carlo simulations demonstrated that the colistin sulfate exposure showed significant negative correlation with renal function.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we used f AUC/MIC ≥20 to evaluate the PTA ( Dudhani et al, 2010b ), which is widely used to optimize the regimen for polymyxin B ( Li et al, 2021b ; Yu et al, 2021 ). The regimen of a 1.0–1.5 million IU daily dose recommended by the current label of colistin sulfate reach PTA ≥90% only for MIC values ≤ 0.5 mg/L, which was in line with a previous study ( Yu et al, 2022 ). High-dose regimens should be considered for the patients infected by organisms with an MIC of ≥1 mg/L.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations